Encephalopathies with KCNC1 variants: genotype-phenotype-functional correlations - Cameron, Jillian M.; Maljevic, Snezana; Nair, Umesh; Aung, Ye Htet; Cogne, Benjamin; Bezieau, Stephane; Blair, Edward; Isidor, Bertrand; Zweier, Christiane; Reis, André; Koenig, Mary Kay; Maarup, Timothy; et al. (Annals of Clinical and Translational Neurology, 2019)
Objective To analyze clinical phenotypes associated with KCNC1 variants other than the Progressive Myoclonus Epilepsy-causing variant p.Arg320His, determine the electrophysiological functional impact of identified variants and explore genotype-phenotype-physiological correlations. Methods Ten cases with putative pathogenic variants in KCNC1 were studied. Variants had been identified via whole-exome sequencing or gene panel testing. Clinical phenotypic data were analyzed. To determine functional impact of variants detected in the K(v)3.1 channel encoded by KCNC1, Xenopus laevis oocyte expression system and automated two-electrode voltage clamping were used. Results Six unrelated patients had a Developmental and Epileptic Encephalopathy and a recurrent de novo variant p.Ala421Val (c.1262C > T). Functional analysis of p.Ala421Val revealed loss of function through a significant reduction in whole-cell current, but no dominant-negative effect. Three patients had a contrasting phenotype of Developmental Encephalopathy without seizures and different KCNC1 variants, all of which caused loss of function with reduced whole-cell currents. Evaluation of the variant p.Ala513Val (c.1538C > T) in the tenth case, suggested it was a variant of uncertain significance. Interpretation These are the first reported cases of Developmental and Epileptic Encephalopathy due to KCNC1 mutation. The spectrum of phenotypes associated with KCNC1 is now broadened to include not only a Progressive Myoclonus Epilepsy, but an infantile onset Developmental and Epileptic Encephalopathy, as well as Developmental Encephalopathy without seizures. Loss of function is a key feature, but definitive electrophysiological separation of these phenotypes has not yet emerged.
CRIS-Team WoS Importer:2019-07-16